PEMBERDAYAAN MASYARAKAT UNTUK BERPARTISIPASI DALAM PELESTARIAN SITUS PATIAYAM DI KABUPATEN KUDUS - Wasino, Widiyati dan (Paramita: Historical Studies Journal, 2011)
The results showed that groups who empowered society are Department of Culture and Tourism is Kudus Regency, Site Conservation Forum Patiayam, interpreters maintained, and the Society of Conservation Society Patiayam Site. Form of empowerment to do is socialize Heritage Law, the socialization of the Master Plan which is equipped with RTBL, to socialize and fossil sites Patiayam, lift the savior maintain Patiayam fossils at the site, and create a mini museum Patiayam site. Studies on community participation suggests that public understanding of the importance of the Patiayam as Heritage Objects, including the criteria to be positive both in terms of preservation Patiayam site. Public awareness in the form of active participation in preserving good sites including Patiayam. Active participation in preserving good sites that carry the impact of the sustainability of the site remains in preventive and curative. ÃÂ Keywords: empowerment, society, sites, patiayam ÃÂ